Ethical practice of evidence-based medicine: A review for plastic surgeons - Rajeev B. Ahuja (Indian Journal of Plastic Surgery)
Last decade has witnessed a spurt in articles focused on the topic of evidence-based medicine (EBM) and medical ethics. These articles are not only educative, but draw attention to the changing scenario of medical practice. Surgeons seem a bit less attentive to practice of EBM, more so in the developing world. The theme is now percolating in our realm for demonstrable incorporation of EBM in our practice, which is allegorical of a good physician and is also likely to become demanding legally. In practicing EBM, several conflicts may arise with the ethical vows of medicine. However, majority of these conflicting issues have germinated from a capitalistic approach to medical practice, where the fear of extraneous compulsions dictating prescriptions and procedures in the garb of ′evidence-based practice′ conflicts ethical behaviour. This review shall appraise the reader with important definitions of medical ethics, EBM and how to incorporate best evidence into ones practice. While, EBM brings objectivity to treatment to derive measurable outcomes it should not become regimented or metamorphose as a pseudonym for defensive medicine to escalate treatment costs. EBM also has several limitations one of which is to place the onus on the practicing physician to search for the best evidence and the other is the resource constraint of practice in the developing world. How a plastic surgery practice could be made to conform to evidence based (EB) procedures is proposed as insufficient surgical skills can pose a serious threat to not only the practice of EB procedures, but to ethical responsibilities as well. In conclusion, it is necessary to incorporate ethical temperance into EB procedures to withstand societal, peer and legal pressures of current times.